SENGKETA PEMBERIAN TANAH WARISAN KEPADA SAUDARI PEREMPUAN BERDASARKAN HUKUM ADAT (WIDA) DI KAMPUNG LAWIR KECAMATAN LANGKE REMBONG KABUPATEN MANGGARAI - Neurus Febrianus Putra Pou (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the regulation of the Wida customary law, the factors causing inheritance land disputes involving female siblings, and the dispute resolution mechanism under customary law in Lawir Village, Langke Rembong District, Manggarai Regency. This research employed an empirical legal method with a qualitative approach. Data were collected through interviews with customary leaders, local government officials, Wida recipients, and community members, supported by literature studies on laws, regulations, and relevant legal references. The findings indicate that Wida is a conditional grant of land to married daughters as a symbol of appreciation and family solidarity within the patrilineal kinship system of the Manggarai community. Disputes generally arise due to the absence of written evidence, the exclusion of all heirs from the granting process, violations of customary agreements, and the increasing economic value of land. Dispute resolution is conducted through customary deliberation involving family members and customary institutions to restore harmony, achieve consensus, and preserve the living values of Manggarai customary law.